Unexpected guests in the tumor microenvironment: microbiome in cancer - Wong-Rolle, Abigail; Wei, Haohan Karen; Zhao, Chen; Jin, Chengcheng (Protein & cell, 2021)
Although intestinal microbiome have been established as an important biomarker and regulator of cancer development and therapeutic response, less is known about the role of microbiome at other body sites in cancer. Emerging evidence has reveale d that the local microbiota make up an important part of the tumor microenvironment across many types of cancer, especially in cancers arising from mucosal sites, including the lung, skin and gastrointestinal tract. The populations of bacteria that reside specifically within tumors have been found to be tumor-type specific, and mechanistic studies have demonstrated that tumor-associated microbiota may directly regulate cancer initiation, progression and responses to chemo- or immuno-therapies. This review aims to provide a comprehensive review of the important literature on the microbiota in the cancerous tissue, and their function and mechanism of action in cancer development and treatment.